Carbon Storage and Greenhouse Gas Emissions from Corporate Social Responsibility-Based Sustainability Projects in Semarang Regency, Indonesia - Dina Banjarnahor; Abner Darmawan Sigar; Nurul Ardian Fitriyani; Irwan Hidayat (Universitas Panji Sakti, 2026)
This study evaluates the environmental impacts of four Corporate Social Responsibility (CSR)-based sustainability projects implemented by a private company producing traditional herbal products in Bergas Kidul Village, Central Java, Indonesia. These CSR projects were intended to mitigate climate change by sequestering carbon in relatively solid forms, thus reducing the emission of greenhouse gases. Reduction of carbon emissions was the main goal to be fulfilled in order to prove that the CSR projects were in line with the corporate commitment to sustainability. The implemented projects included avocado tree plantations, communal cattle farming, organic fertilizer application, and the reuse of high-density polyethylene (HDPE) drums. This research aimed to assess and estimate the carbon balance of these four practices based on the potential greenhouse gases stored and emitted by each practice. Supporting data were collected through surveys, interviews, and literature studies. Data were then analyzed using the 2006 and 2019 IPCC Guidelines for National Greenhouse Gas Inventories, specifically using the Tier 1 method. The Tier 1 approach employs the basic method and the default emission factors provided in the IPCC Guidelines (Workbook and Reference Manual). Based on this analysis, avocado plantations were estimated to sequester 79.850 ton per year of CO2 eq but cattle farming generated 19.91 ton per year of CO2 eq. The use of organic fertilizer in paddy fields was estimated to emit around 0.0005 kg of N2O per hectare (0.1325 kg of CO2 eq per hectare), and this seemed to be drastically reduced compared to the application of chemical fertilizers. Applying liquid organic fertilizer was estimated to reduce approximately 74.518 kg of CO2 eq per hectare. Meanwhile, reusing 46 HDPE drums as planting medium for the household food security project in the studied area, instead of burning them, was predicted to store approximately 1.583 tons of CO2 eq in the solid form. While we couldn’t conclude a single net carbon balance resulted from these projects due to methodological limitations, these results could depict the potential and risks of environmental impacts of the claimed sustainability interventions for a longer period.